Down home, on a different range - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Introduction to Range Management in Free and Open Access Environments of Sub-Saharan Africa. E Tedonkeng Pamo and R D Pieper. Sitmex, Express-Services and CTA co-publication. 2000. 152 pp. CTA number 1023. 20 credits points.